Concentrations and risks of p‐dichlorobenzene in indoor and outdoor air. (18th July 2012) - Chin, J.‐Y.; Godwin, C.; Jia, C.; Robins, T.; Lewis, T.; Parker, E.; Max, P.; Batterman, S.
<x xml:space="preserve">Abstract</x> Abstract p‐dichlorobenzene (PDCB) is a chlorinated volatile organic compound that can be encountered at high concentrations in buildings owing to its use as pest repellent and deodorant. This study characterizes PDCB concentrations in four communities in southeast Michigan. The median concentration outside 145 homes was 0.04 μg/m3, and the median concentration inside 287 homes was 0.36 μg/m3. The distribution of indoor concentrations was extremely skewed. For example, 30% of the homes exceeded 0.91 μg/m3, which corresponds to a cancer risk level of 10−5 based on the California unit risk estimate, and 4% of homes exceeded 91 μg/m3, equivalent to a 10−3 risk level. The single highest measurement was 4100 μg/m3. Estimates of whole‐house emission rates were largely consistent with chamber test results in the literature. Indoor concentrations that exceed a few μg/m3 indicate the use of PDCB products. PDCB concentrations differed among households and the four cities, suggesting the importance of locational, cultural, and behavioral factors in the use patterns of this chemical. The high PDCB levels found suggest the need for policies and actions to lower exposures, for example, sales or use restrictions, improved labeling, and consumer education. Practical Implications Distributions of p‐dichlorobenzene concentrations in residences are highly right‐skewed, and a subset of houses has very elevated concentrations that are equivalent to an excess cancer risk of 10−3 or higher based on the California unit risk effect estimate. House‐to‐house variation is large, reflecting differences in use practices. Stronger policies and educational efforts are needed to eliminate or modify indoor usage practices of this chemical.